The scientific background of competitive maize production - Nagy, János; Széles, Adrienn (Acta Agraria Debreceniensis, 2018)
The effect and interaction of crop production factors on maize yield has been examined for nearly 40 years at the Látókép Experiment Site of the University of Debrecen in a long-term field experiment that is unique and acknowledged in Europe. The research aim is to evaluate the effect of fertilisation, tillage, genotype, sowing, plant density, crop protection and irrigation. The analysis of the database of the examined period makes it possible to evaluate maize yield, as well as the effect of crop production factors and crop year, as well as the interaction between these factors. Based on the different tillage methods, it can be concluded that autumn ploughing provides the highest yield, but its effect significantly differed in irrigated and non-irrigated treatments. The periodical application of strip tillage is justified in areas with favourable soil conditions and free from compated layers (e.g. strip – strip – ploughing – loosening). Under conditions prone to drought, but especially in several consecutive years, a plant density of 70–80 thousand crops per hectare should be used in the case of favourable precipitation supply, but 60 thousand crops per hectare should not be exceeded in dry crop years. The yield increasing effect of fertilisation is significant both under non-irrigated and irrigated conditions, but it is much more moderate in the non-irrigated treatment. Selecting the optimum sowing date is of key importance from the aspect of maize yield, especially in dry crop years. Irrigation is not enough in itself without intensive nutrient management, since it may lead to yield decrease. The results of research, development and innovation, which are based on the performed long-term field experiment, contribute to the production technological methods which provide an opportunity to use sowing seeds, fertilisers and pesticides in a regionally tailored and differentiated way, adapted to the specific needs of the given plot, as well as to plan each operation and to implement precision maize production.